A Rare Case: HaemoglobinS-Thalassemia in Adult - Linny Luciana; Ninik Sukartini (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2023)
Hemoglobinopathy refers to a disease involving a qualitative or quantitative defect of the structure or synthesis of haemoglobin molecules. The HaemoglobinS- beta thalassemia occurs in a heterozygotes individual with beta-thalassemia and HaemoglobinS gene. A 29-year-old man came with severe anemia, thrombocytopenia, and history of repeated blood transfusions. Physical examination showed pale conjunctiva, pansystolic murmurs, and hepatosplenomegaly. The HaemoglobinS fraction was found in haemoglobin electrophoresis with increased HaemoglobinF and decreased HaemoglobinA2 fraction. The peripheral blood smear shows abnormal erythrocytes morphologies such as pencil shapes, fragmentocytes, target cells, and sickle shapes. The patient was diagnosed with chronic anaemia caused by HaemoglobinS-beta thalassemia. It makes ineffective erythropoiesis, intravascular, and extravascular hemolysis. This haemoglobinopathy caused increased ferritin and transferrin saturation. The presence of renal failure indicate there is a complicated condition like microvascular obstruction of renal. In this case, there is a reduction of HaemoglobinA2 fraction that is not common in HaemoglobinS-beta thalassemia. The patient with Haemoglobin S / beta+ thalassemia shows intravascular hemolysis, ineffective hematopoiesis, and vaso-occlusive signs. Deoxyribo Nucleic Acid analysis is further needed to confirm the combination defect of haemoglobin synthesis disorders in conjunction with alpha thalassemia or Hereditary persistence of fetal haemoglobin.